2008
DOI: 10.3746/jkfn.2008.37.11.1422
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Mineral and Heavy Metal Contents in the Hair of Preschool Aged Autistic Children

Abstract: The purpose of this study was to test characteristics between normal and autistic children via comparison of nutrient intakes, hair mineral, blood free radical, and serotonin contents. A total of 50 children aged 3-9 were divided into two main groups of normal control children (n=22) and autistic children (n=28) tested by child psychiatrist. The nutrient intakes by 24-hour recall method were no significantly different between the two groups. The concentrations of toxic mineral, such as cadmium (Cd) and lead (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The characteristics of the studies included in the meta-analysis are shown in Table 1 . The meta-analysis of Pb levels in hair included 17 studies [ 19 , 32 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], 13 studies in whole blood [ 20 , 31 , 34 , 44 , 58 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ], and 8 studies in urine [ 24 , 34 , 36 , 58 , 70 , 71 , 72 , 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of the studies included in the meta-analysis are shown in Table 1 . The meta-analysis of Pb levels in hair included 17 studies [ 19 , 32 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], 13 studies in whole blood [ 20 , 31 , 34 , 44 , 58 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ], and 8 studies in urine [ 24 , 34 , 36 , 58 , 70 , 71 , 72 , 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding Pb levels in hair, four studies were conducted in Europe [ 32 , 49 , 53 , 58 ], two studies in North America [ 54 , 60 ], eight studies in Asia [ 19 , 47 , 48 , 51 , 55 , 56 , 59 , 61 ], and three studies in Africa [ 50 , 52 , 57 ]. Regarding Pb levels in whole blood, two studies were carried out in Europe [ 58 , 62 ], two studies in North America [ 34 , 64 ], one study in Central America [ 65 ], five studies in Asia [ 31 , 44 , 63 , 68 , 69 ], and three studies in Africa [ 20 , 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation